2021
DOI: 10.1002/ajcp.12549
|View full text |Cite
|
Sign up to set email alerts
|

Mentoring Children in Foster Care: Examining Relationship Histories as Moderators of Intervention Impact on Children’s Mental Health and Trauma Symptoms

Abstract: Highlights• Children's early relational histories may affect the impact of mentoring programs.• Fostering Healthy Futures (FHF) improves mental health of children with varied relational histories.• FHF's impact on trauma symptoms was stronger for children with fewer caregiver changes pre-program.• FHF's impact on quality of life was stronger for children with fewer caregiver changes pre-program.• FHF's impact on quality of life was stronger for children with poorer birth parent relationships.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 84 publications
(89 reference statements)
0
2
0
1
Order By: Relevance
“…For example, some studies suggest that youth who have experienced fewer environmental and individual risk factors or more moderate levels of challenges tend to experience stronger mentoring relationships and reap more positive benefits from program participation than those experiencing higher levels of risk (Poon et al, 2022; Raposa et al, 2016; Schwartz et al, 2011; Weiler et al, 2019). Yet other research indicates mixed associations or a lack of association between baseline risk and mentoring effects on youth outcomes (DuBois et al, 2011; Taussig et al, 2013; Weiler et al, 2022), and at least one study suggests that mentored youth with higher levels of individual risk may actually derive greater benefits than those with lower levels of risk (Herrera et al, 2013). These mixed results may be attributable to the broad range of individual and environmental factors characterized as “risk,” suggesting the value of a more targeted approach to studying the role of specific youth characteristics or experiences that may influence both the processes and impacts of mentoring.…”
Section: Discussionmentioning
confidence: 99%
“…For example, some studies suggest that youth who have experienced fewer environmental and individual risk factors or more moderate levels of challenges tend to experience stronger mentoring relationships and reap more positive benefits from program participation than those experiencing higher levels of risk (Poon et al, 2022; Raposa et al, 2016; Schwartz et al, 2011; Weiler et al, 2019). Yet other research indicates mixed associations or a lack of association between baseline risk and mentoring effects on youth outcomes (DuBois et al, 2011; Taussig et al, 2013; Weiler et al, 2022), and at least one study suggests that mentored youth with higher levels of individual risk may actually derive greater benefits than those with lower levels of risk (Herrera et al, 2013). These mixed results may be attributable to the broad range of individual and environmental factors characterized as “risk,” suggesting the value of a more targeted approach to studying the role of specific youth characteristics or experiences that may influence both the processes and impacts of mentoring.…”
Section: Discussionmentioning
confidence: 99%
“…Grossman and Rhodes (2002) found that youth who were more sensitive to rejection actually formed longer‐lasting mentoring relationships. In a mentoring program for youth in foster care, youth who had poorer‐quality relationships with birth parents experienced stronger program benefits on their overall quality of life, perhaps because these youth had a greater need for support from a caring adult (Weiler et al, 2022).…”
Section: The Importance Of Relationship Quality and Lengthmentioning
confidence: 99%
“…El sistema común está constituido por un padre, una madre, hijos e hijas que nacen al formar una relación amorosa. Cada familia posee grado de parentesco y características únicas (Gómez et al, 2012;Weiler et al, 2021). Dentro de esta esfera puede haber ciertos factores de protección o de peligro para cada sujeto que la integran (Irarrázaval & Prieto, 2016).…”
Section: Introductionunclassified